2010
DOI: 10.3386/w16518
|View full text |Cite
|
Sign up to set email alerts
|

Is Poor Fitness Contagious? Evidence from Randomly Assigned Friends

Abstract: The increase in obesity over the past thirty years has led researchers to investigate the role of social networks as a contributing factor. However, several challenges make it difficult to demonstrate a causal link between friends' physical fitness and own fitness using observational data. To overcome these problems, we exploit data from a unique setting in which individuals are randomly assigned to peer groups. We find statistically significant peer effects that are 40 to 70 percent as large as the own effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 28 publications
(28 reference statements)
5
78
1
Order By: Relevance
“…Similarly, we do not report outcomes, such as the choice of major at business school or career choice afterwards, which might be influenced by a student's peers. We also do not examine whether social behavior such as academic cheating (Carrell, Malmstrom, and West 2008), smoking (Nakajima 2007) or fitness (Carrell, Hoekstra, and West 2011) is differentially affected by study group or residential peers.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, we do not report outcomes, such as the choice of major at business school or career choice afterwards, which might be influenced by a student's peers. We also do not examine whether social behavior such as academic cheating (Carrell, Malmstrom, and West 2008), smoking (Nakajima 2007) or fitness (Carrell, Hoekstra, and West 2011) is differentially affected by study group or residential peers.…”
Section: Resultsmentioning
confidence: 99%
“…1 For examples, see: Bandiera and Rasul (2006) ;Bayer, Ross, and Topa (2008) ;Bertrand, Luttmer, and Mullainathan (2000) ;Carrell, Malmstrom, and West (2008); Case and Katz (1991) ;Evans, Oates, and Schwab (1992); Gaviria and Raphael (2001) ;Glaeser, Sacerdote, and Scheinkman (1996); Hensvik and Nilsson (2010); Markussen and Røed (2012); Maurin and Moschion (2009) ;Monstad, Propper, and Salvanes (2011);Munshi (2003); and Rege, Telle, and Votruba (2012). 2 See, for example: Babcock et al (2011);Rasul (2009, 2010); Carrell, Fullerton, and West (2009) ;Carrell and Hoekstra (2010) ;Carrell, Hoekstra, and West (2011) ;Carrell, Sacerdote, and West (2011);Cullen, Jacob, and Levitt (2006); Duncan et al (2005); Hanushek et al (2003); Hoxby (2000); Imberman, Kugler, In contrast, we focus on peer influence in naturally occurring groups and exploit variation in the "price" of a social program for a random s...…”
mentioning
confidence: 99%
“…(Lyons, 2011, Cohen-Cole and Fletcher, 2008a, Cohen-Cole and Fletcher, 2008b, Noel and Nyhan, 2011, Sainsbury, 2008, Shalizi and Thomas, 2011). Nevertheless, other recent studies, using random assignment of peers, have identified a direct causal link between individual and peer physical activity (Carrell et al, 2011). …”
Section: Discussionmentioning
confidence: 99%